Mobilizing 'context': Vocabulary checks in ESL tutoring sessions. (July 2022) - Duran, Derya; Jakonen, Teppo
Abstract: This study investigates the practice of unplanned and emergent vocabulary checks, i.e. turns through which a speaker explicitly checks whether the recipient knows a word, in small-group tutorial instruction. The data are video-recorded English as a second language (ESL) tutoring sessions between a native English speaker tutor and ESL students at an urban community college in the United States. By drawing on conversation analysis, we analyze how vocabulary checks emerge sequentially and with the help of contextual interactional resources. Findings suggest that vocabulary checks constitute a practice for managing both shared understanding and pedagogical concerns. By singling out a vocabulary item as possibly unknown to the student, the tutor can attend to weak signals for a student's non-understanding and orient to having epistemic primacy over the English language, thereby "talking into being" the role of a language expert. The checks pave way for vocabulary teaching moments by making word definitions and explanations interactionally relevant, which provides opportunities for language learning. The study highlights the intricate relationship between context, intersubjectivity and pedagogy in small-group tutoring contexts, an awareness of which can help practitioners reflect on the role of contextual resources in their teaching.